2003
DOI: 10.1021/es026211g
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic in Groundwater in Eastern New England:  Occurrence, Controls, and Human Health Implications

Abstract: In eastern New England, high concentrations (greater than 10 microg/L) of arsenic occur in groundwater. Privately supplied drinking water from bedrock aquifers often has arsenic concentrations at levels of concern to human health, whereas drinking water from unconsolidated aquifers is least affected by arsenic contamination. Water from wells in metasedimentary bedrock units, primarily in Maine and New Hampshire, has the highest arsenic concentrations-nearly 30% of wells in these aquifers produce water with ars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
134
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(144 citation statements)
references
References 14 publications
6
134
2
Order By: Relevance
“…The wider range of total As concentrations on the sediments is consistent with the hypothesis that As not associated with coatings on sediment grains is in the interior of mineral grains and that the range of values reflects heterogeneity in the distribution of these grains in the sediments. Studies of As in drinking water supplies elsewhere in New England 88,89 concluded that, in aquifers where elevated As concentrations were observed, As was ultimately derived from pyrite and other sulfide minerals, which, in contrast to silicate minerals, typically have significant concentrations of As.…”
Section: Origin and Chemical Forms Of Arsenic In The Sedimentsmentioning
confidence: 99%
“…The wider range of total As concentrations on the sediments is consistent with the hypothesis that As not associated with coatings on sediment grains is in the interior of mineral grains and that the range of values reflects heterogeneity in the distribution of these grains in the sediments. Studies of As in drinking water supplies elsewhere in New England 88,89 concluded that, in aquifers where elevated As concentrations were observed, As was ultimately derived from pyrite and other sulfide minerals, which, in contrast to silicate minerals, typically have significant concentrations of As.…”
Section: Origin and Chemical Forms Of Arsenic In The Sedimentsmentioning
confidence: 99%
“…The heavy metal cadmium (Cd) and the metalloid arsenic (As) are examples of elemental pollutants with a high affinity for thiols (Li et al, 2004). Arsenic pollution is widespread in the environment, and contamination of As in drinking water and food is a significant human health concern (Ayotte et al, 2003;Dhankher, 2005). The oxyanion arsenite (AsO 3 23 ) contains As in its trivalent form (As +3 or As III ) and is highly thiol reactive.…”
Section: Introductionmentioning
confidence: 99%
“…The actual valence states and chemical form, however, depend on the redox environments in the water systems including pH, oxidation-reduction potential, and the presence of complexing ions. 7,8 Toxic arsenic compounds have been detected in water supply wells in the United States 9 and abroad. The shallow groundwater, a major source of drinking water for many south and southeast Asian countries like Bangladesh, is contaminated with arsenic.…”
mentioning
confidence: 99%